Androgen Secreting Steroid Cell Tumor of the Ovary Represented with Postmenopasal Bleeding and Extensive Hirsutism - Georgievska, Jadranka; Antovska, Vesna; Basheska, Neli; Aleksioska, Natasha (Scientific Foundation SPIROSKI, 2013)
Introduction: Steroid cell tumors of the ovary present less than 0.1% of all ovarian tumors and belong in the group of sex cord-stromal tumors. Case description: We present a case of 69-year-old woman investigated because of postmenopausal bleeding, a 5-year history of excessive hirsutism, baldness and acne. The evaluation revealed elevated serum testosterone, but ultrasound detected a 2 cm mass of the left ovary. The patient underwent hysterectomy and bilateral adnexectomy. The histopathology diagnosis was steroid cell tumor, not otherwise specified. Postoperative chemotherapy was administered at the discretion of the radio-oncologist. At the last follow-up 48 months after surgery, the hirsutism was completely resolved, the serum testosterone was within the normal range and there was no evidence of recurrence. Conclusion: In adult patients with hirsutism and elevated serum testosterone a possibility of a presence of an ovarian steroid cell tumor should be considered. Surgery is the main treatment of such patients.
Keywords: hirsutism; steroid cell tumor; ovary; testosterone; laparoscopy